Discalculia y su repercusión en el aprendizaje del área de matemática a estudiantes de la Unidad Educativa “Réplica Eugenio Espejo” Parroquia Clemente Baquerizo, Cantón Babahoyo, Provincia los Ríos. - Mera Troya, Mariela Elizabeth (2017)
The present research work is a very important alternative whose main purpose is to develop strategies that help the student to improve their learning, because the problems they present with mathematical operations are known by the teacher and it is vital that they apply coherent activities to that education be effective. With the passage of time the dyscalculia will grow in each of the students and therefore in teaching learning, making difficulties greater, limiting them in the development of mathematical calculations, their skills and abilities will not be satisfactory. It is therefore very important that the teacher is trained and acquires current knowledge, seeks to motivate learning in all areas, especially mathematics and everything that relates to their teaching. Chapter One reveals the subject of research, and how the problem has developed globally, specifically in Ecuador, in the Province and the most essential in the Replica Eugenio Espejo Educational Unit. Chapter two reflects the theoretical or referential framework, determining the hypothesis. In Chapter Three the results of the research using the survey will be analyzed as a method to make possible the final report of the project. Chapter 4 presents the application proposal.